2014
DOI: 10.1115/1.4028270
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Nano-Biomaterial Applications for Heavy Oil Recovery in Shaly Porous Models: A Pore-Level Study

Abstract: Application o f nano or biomaterials for enhanced oil recovery (EOR) has been recently much attended by petroleum engineering researchers. However, how would be the displacement mecha nisms and how would change the recovery efficiency while nano and biomaterials are used simultaneously is still an open question. To this end, a series o f injection tests performed on micromodel containing shale strikes. Three types o f biomaterials including biosurfactant, bioemulsifier, and biopolymer beside two types of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Recent studies have pointed out advantages of utilizing nanofluids as EOR agents, which have not been considered enough (Fletcher and Davis 2010;Rezvani et al 2017). Generally, the underlying mechanisms of improving oil recovery by injecting nanoparticles fall into six categories, including: (1) establishing disjoining pressure to aid detachment of oil drops from the pore surface (Chengara et al 2004;Mcelfresh et al 2012;Wasan et al 2011), (2) plugging pore channels (Hashemi et al 2013;Idogun et al 2016;Sun et al 2017;Zamani et al 2012), (3) enhancing sweep efficiency by decreasing the mobility of the displacing fluid (Al-Anssari et al 2016;Salem Ragab and Hannora 2015;Tarek and El-Banbi 2015), (4) altering rock wettability toward water-wet conditions (Hendraningrat and Torsaeter 2014a;Hendraningrat and Torsaeter 2014b;Karimi et al 2012;Li et al 2015;Mohebbifar et al 2015), (5) reducing interfacial tension (IFT) between residual oil and injecting fluids (Alomair et al 2014;Hendraningrat et al 2013a;Salem Ragab and Hannora 2015;Torsater et al 2012) and (6) preventing/retarding asphaltene precipitation by the action of nanoparticles (Haindade et al 2012;Kazemzadeh et al 2015;Nassar et al 2012;Tarboush and Husein 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have pointed out advantages of utilizing nanofluids as EOR agents, which have not been considered enough (Fletcher and Davis 2010;Rezvani et al 2017). Generally, the underlying mechanisms of improving oil recovery by injecting nanoparticles fall into six categories, including: (1) establishing disjoining pressure to aid detachment of oil drops from the pore surface (Chengara et al 2004;Mcelfresh et al 2012;Wasan et al 2011), (2) plugging pore channels (Hashemi et al 2013;Idogun et al 2016;Sun et al 2017;Zamani et al 2012), (3) enhancing sweep efficiency by decreasing the mobility of the displacing fluid (Al-Anssari et al 2016;Salem Ragab and Hannora 2015;Tarek and El-Banbi 2015), (4) altering rock wettability toward water-wet conditions (Hendraningrat and Torsaeter 2014a;Hendraningrat and Torsaeter 2014b;Karimi et al 2012;Li et al 2015;Mohebbifar et al 2015), (5) reducing interfacial tension (IFT) between residual oil and injecting fluids (Alomair et al 2014;Hendraningrat et al 2013a;Salem Ragab and Hannora 2015;Torsater et al 2012) and (6) preventing/retarding asphaltene precipitation by the action of nanoparticles (Haindade et al 2012;Kazemzadeh et al 2015;Nassar et al 2012;Tarboush and Husein 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Except for the aforementioned core flooding tests, the glass micromodel experiment is a major means used in the study of the microscopic recovery of oils during nanofluid flooding [34,44,45,55]. By this kind of glass micromodel, the microscopic behavior of oil and nanofluid two-phase flow and fluid distribution in porous media can be continuously monitored during the experiments.…”
Section: Glass Micromodel Experimentsmentioning
confidence: 99%
“…For fractured limestones, AlAnssari et al [28] found that the SiO2 nanofluids induced wettability alteration on oil-wet and mixedwet calcite substrates, consistent with the results of Roustaei and Bagherzadeh. In addition, Mahdi et al [44] found that nano-biomaterials have the ability to alter the wettability of shale from oil-wet to Figure 9. Relative permeability curves.…”
Section: Wettability Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy oil and oil sands reservoirs contain shale layers as flow barriers with almost zero permeability [4], These shale layers have great impact on steam chamber expansion [5], Limited geo physical data of unconsolidated oil sands give additional uncer tainty. The continuous dynamic data are useful in reducing uncertainties of reservoir models [6-8], However, it is difficult to apply dynamic data in initial production period.…”
Section: Introductionmentioning
confidence: 99%